Digital Eye Strain among Peruvian Nursing Students: Prevalence and Associated Factors. - Huyhua Gutierrez, S.C. (2023)
There has been a high prevalence of digital eye strain (DES) among students who have received distance-learning lessons due to COVID-19. However, in low- and middle-income countries, there are few studies that have analyzed its associated factors. This study aimed to determine the prevalence of DES and its associated factors among nursing students during COVID-19 distance learning. This was a cross-sectional analytical study conducted between May and June 2021 in six Peruvian universities. The sample comprised 796 nursing students. DES was measured using the Computer Vision Syndrome Questionnaire (CVS-Q). A bivariate logistic regression analysis was performed. DES was found in 87.6% of nursing students. Sitting upright (OR, 0.47; 95% IC, 0.30–0.74), using electronic devices for more than four hours a day (OR, 1.73; 95% IC, 1.02–2.86), not following the 20-20-20 rule (OR, 2.60; 95% IC, 1.25–5.20), having the screen brightness very high (OR, 3.36; 95% IC, 1.23–11.8), and not wearing glasses (OR, 0.59; 95% IC, 0.37–0.93) are factors associated with DES. The prevalence of DES among nursing students is high. Improving the ergonomics of study environments, reducing the time of exposure to electronic devices, adjusting the screen brightness, and taking eye-care measures are key to controlling computer vision syndrome in virtual learning.